Assessment of Food Frequency Intake and Dietary Habits for Diabetic Pregnant Women - Ahmmad, suad; Abdulwahid, hala (Iraqi National Journal of Nursing Specialties, 2015)
Objective: The study aims at assessing the food frequency intake and dietary habits for diabetic pregnant women. Methodology: A descriptive study is carried out for the period from November4th 2013 to August 25th 2014. A purposive "non-probability" sample of one hundred diabetic pregnant women is selected from the Diabetic and Endocrine Center in Al-Amarha City. A questionnaire is developed as a tool of data collection. Content validity of the study instrument is determined through panel of experts. Split-half reliability technique is used for reliability determination of the study instrument which depicts a reliability coefficient of (0.79) for the entire scale. A structured interview with each diabetic pregnant woman is applied for data collection. Data are analyzed through the application of descriptive statistical data analysis approach of frequency, percent and standard deviation and inferential statistical data analysis approach of linear regression. Results: The results of the study indicated that the vast majority of pregnant women have acceptable level of food frequency intake and dietary habits. Being them pregnant with diabetes, they need to have more than acceptable level so they can go through a healthy and safe pregnancy, as well as labor and having a healthy baby without complications. Recommendations: The study recommends for the initiation of collaboration and coordination between the Nutrition Research Institute and the Diabetic and Endocrine Center in Al-Amara City concerning the diabetic pregnant women and their dietary patterns. Further study can be conducted on a large sample size and nation-wide base.